Seismic risk assessment and mitigation analysis of large public school building portfolios in Metro Manila. Issue 3 (August 2022) - Jeswani, Kevin; Guo, Jack; Christopoulos, Constantin
This article presents an integrated framework for portfolio seismic risk assessment. The framework includes a systematic approach to the collection and categorization of exposed assets, and a robust method that combines vulnerabilities of different levels of resolution, including detailed vulnerabilities based on Federal Emergency Management Agency (FEMA) P-58 and REDi analyses, to produce efficient portfolio-level assessment. The vulnerability information encodes risk information that directly addresses the decision-support needs of stakeholders, including the benefits of seismic retrofit. The proposed framework is applied to a spatially distributed infrastructure portfolio composed of over 1000 public school buildings across Makati and Quezon City, in the Metro Manila region in Philippines, to demonstrate the value of portfolio-level seismic risk mitigation strategies. This study illustrates that the proposed regional seismic risk assessment approach can provide more reliable regional risk assessments in a computationally efficient manner and is able to quantify different risk contributors and identify cost-drivers that can be targeted for performance-based risk management of large portfolios.